Assessment of the Applicability and Steps of Implementing the Six Sigma Method in the Quality Management System of Additive Manufacturing - Ivan S. Kushnir; Anna P. Adylina; Tatyana A. Levina (RUDN Journal of Engineering Research)
Despite the widespread introduction of 3D printing in machine-building industries within the framework of Industry 4.0, the quality of manufactured products currently requires regulation and improvement. To reduce the volume of defects and increase the fault tolerance of the product, improve the condition of the workplace, work convenience, accounting for finished products and other important factors of the high-quality production cycle, there are a sufficient number of methods and practices used in many fields (automotive, mechanical engineering, energy, etc.). One of these methods is DMAIC, which involves the introduction of the 6 sigma method into the technological sphere of additive manufacturing product quality management in order to improve its quality at these enterprises. The “define-measure-analyze-improve-control” cycle is used by the author in the context of this study to analyze the possible optimization of production procedures at additive manufacturing enterprises by selective laser melting (SLM). The analysis of production practices and suggestions for improving the quality of manufactured products, based on the DMAIC, method, will improve the current additive manufacturing processes at large technological enterprises and will be able to positively affect the quality characteristics of products. With the help of a technological approach based on the DFSS cycle, through the application of each step sequentially, an effective change in the positive side of quality as the production process itself is possible: the manufacturing accuracy increases at each stage, the process is modernized with each new cycle, based on previous results; as well as finished products: the number of defects decreases, the mechanical characteristics of products improve.